A novel OSA-related model of intermittent hypoxia in endothelial cells under flow reveals pronounced inflammatory pathway activation - Müller, Martin B.; Stihl, Clemens; Schmid, Annika; Hirschberger, Simon; Mitsigiorgi, Rea; Holzer, Martin; Patscheider, Martin; Weiss, Bernhard G.; Reichel, Christoph; Hübner, Max; Uhl, Bernd (Frontiers in Physiology, 2023)
Obstructive sleep apnea (OSA) is a common sleep-related breathing disorder characterized by recurrent episodes of upper airway obstruction and subsequent hypoxia. In patients with OSA, severity and number of these hypoxic events positively correlate with the extent of associated cardiovascular pathology. The molecular mechanisms underlying intermittent hypoxia (IH)-driven cardiovascular disease in OSA, however, remain poorly understood – partly due to the lack of adequate experimental models. Here, we present a novel experimental approach that utilizes primary human endothelial cells cultivated under shear stress. Oxygen partial pressure dynamics were adopted in our in vitro model according to the desaturation-reoxygenation patterns identified in polysomnographic data of severe OSA patients (n=10, with 892 severe desaturations, SpO2<80%). Using western blot analysis, we detected a robust activation of the two major inflammatory pathways ERK and NF-κB in endothelial cells, whereas no HIF1α and HIF2α protein stabilization was observed. In line with these findings, mRNA and protein expression of the pro-inflammatory adhesion and signaling molecule ICAM-1 and the chemokine CCL2 were significantly increased. Hence, we established a novel in vitro model for deciphering OSA-elicited effects on the vascular endothelium. First data obtained in this model point to the endothelial activation of pro-inflammatory rather than hypoxia-associated pathways in OSA. Future studies in this model might contribute to the development of targeted strategies against OSA-induced, secondary cardiovascular disease.